Analisis Hukum Terhadap Motif Pengembalian Uang Negara Pasca Investigasi Korupsi - Mangar, Irma; Shinta Azhra Sudrajat; Malaika Putri Wardhani (Diktum: Jurnal Ilmu Hukum, 2026)
This study aims to analyze the legal arrangements regarding the return of state losses in corruption crimes in Indonesia and examine the motives for state refunds by post-investigation officials and their implications for law enforcement. The research method used is normative legal research with legislative, conceptual, and case approaches. The legal materials used include primary, secondary, and tertiary legal materials that are qualitatively analyzed. The results of the study show that normatively, legal arrangements regarding the return of state losses have been comprehensively regulated through various instruments, such as payment of compensation, asset forfeiture, and civil lawsuits. This arrangement contributes to supporting the state's financial recovery, strengthens the legal restorative function, and provides a preventive effect against corruption. However, in its implementation, there are still various obstacles, such as limitations in asset tracking and recovery, weak coordination between law enforcement agencies, and not optimal asset recovery-based approach. In addition, the motive for state refunds after a corruption investigation is not always based on legal awareness, but is often influenced by pragmatic considerations, legal pressure, and reputational interests.